The relationship between macroeconomic variables towards Islamic stock market in Malaysia / Nurul Ain Ali Mokhtar - Ali Mokhtar, Nurul Ain (Faculty of Business and Management, 2017)
This study is to analyze the relationship between macroeconomic variables towards Islamic stock market in Malaysia. The purpose of this study is to observe this relationship in Malaysian context. In order to achieve the objective, an estimation of E-views is used to run and test the regression analysis for this study. The variables used are FBM Emas Shariah Index (FTSE) as the proxy for Islamic stock market, Composite Price Index (CPI) as the proxy for inflation rate, Industrial Production Index (IPI) as the proxy for gross domestic product and Financial Aggregate Supply (M3) as the proxy for money supply. This study used quarterly data from first quarter of 2009 until second quarter of 2016 taken from authorized sources. The findings showed that Islamic stock market volatility is co-integrated with the selected macroeconomic variables in which FTSE is related positively and significantly with IPI, CPI and M3.